2019
DOI: 10.1021/acssuschemeng.9b02772
|View full text |Cite
|
Sign up to set email alerts
|

Hexane-1,2,5,6-tetrol as a Versatile and Biobased Building Block for the Synthesis of Sustainable (Chiral) Crystalline Mesoporous Polyboronates

Abstract: We report on the synthesis and characterization of novel mesoporous chiral polyboronates obtained by condensation of ( R , S )/( S , S )-hexane-1,2,5,6-tetrol (HT) with simple aromatic diboronic acids (e.g., 1,3-benzenediboronic acid) (BDB). HT is a cellulose-derived building block comprising two 1,2-diol structures linked by a flexible ethane bridge. It typically consists of two diastereomers one of which [( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The tetrol diastereomer ratio, determined by the starting LGOL threo/erythro ratio and by which intermediates (DDM and DDG, or DDF) are formed during the reaction, is an important property as it could influence the physical–chemical properties of tetrol-derived materials . For example, recently, De bruyn et al demonstrated that the diastereomeric excess of tetrol affected the surface areas and the porosities of the resulting chiral porous polyboronates obtained by reaction of tetrol and aromatic boronic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The tetrol diastereomer ratio, determined by the starting LGOL threo/erythro ratio and by which intermediates (DDM and DDG, or DDF) are formed during the reaction, is an important property as it could influence the physical–chemical properties of tetrol-derived materials . For example, recently, De bruyn et al demonstrated that the diastereomeric excess of tetrol affected the surface areas and the porosities of the resulting chiral porous polyboronates obtained by reaction of tetrol and aromatic boronic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Channeling the production of commodity chemicals from petroleum-derived resources to renewable lignocellulosic feedstocks is a great route to the effective transitioning of the chemical industry toward materials and products with a lower CO 2 footprint. Biomass-derived monomers can be used as important platform molecules for the synthesis of polymers, resins, solvents, surfactants, among others. Sugar derivatives have been shown to offer many opportunities to obtain such platform molecules. , Levoglucosenone (LGO) is a biobased sugar-like compound, which can be produced from cellulose by mild pyrolysis. Notably, based on the pyrolytic method developed by the Circa Group, an actual 1000 ton LGO/year plant is currently being developed in France . LGO can also be produced at yields up to 51% using polar aprotic solvents and sulfuric acid at 170–230 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently demonstrated how Lgol can be selectively converted into tetrol . Tetrol is a polyol of industrial interest, ,, which could be potentially useful to the synthesis of a range of polymers. , Also, since the molecule displays two chiral centers, it can have potential uses as a chiral synthon . Tetrol is obtained by the selective C–O cleavage of the anhydrobridge of Lgol in water over a Brønsted acid catalyst, forming the dideoxy sugar intermediates 3,4-dideoxymannose (DDM) from t-Lgol and 3,4-dideoxyglucose (DDG) from e-Lgol.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis of levoglucosanol forms 3,4-dideoxy sugar intermediates that are then hydrogenated to a mixture of (2 R ,5 S )-1256-HTet and (2 S ,5 S )-1256-HTet. De bruyn and co-workers synthesized chiral mesoporous polyboronates from 1256-HTet, showing that the stereochemistry of 1256-HTet influences the porosity properties of these materials …”
Section: Introductionmentioning
confidence: 99%
“…De bruyn and co-workers synthesized chiral mesoporous polyboronates from 1256-HTet, showing that the stereochemistry of 1256-HTet influences the porosity properties of these materials. 27 Polyol-based nonionic surfactants, comprised of a hydrophilic polyol head group and hydrophobic tail, have gained attention for cosmetics and pharmaceuticals applications because of their biodegradability and nontoxicity. Key properties, such as hydrophilicity and phase behavior, are a strong function of the number, positions, and stereochemistry of hydroxyl groups.…”
Section: ■ Introductionmentioning
confidence: 99%